Work‐related injuries to animal care workers, Washington 2007–2011. Issue 3 (17th December 2015) - Fowler, Heather; Adams, Darrin; Bonauto, David; Rabinowitz, Peter
Abstract : Background: For workers engaged in animal care, workplace hazards are common and may outnumber those experienced by human healthcare workers. Methods: We used accepted Washington State workers' compensation claims for the period from January 1, 2007 and December 31, 2011 to compare injury rates and types of injuries across animal care occupations. Results: Work‐related injuries frequently affect veterinary support staff and those working in pet stores, shelters, grooming facilities and kennels. Animal‐related injuries were the most commonly reported injury type experienced by all groups, though the animal source of injury appears to differ by work setting. Conclusions: Workplace related injuries among animal care workers are common and most often caused by physical insults resulting from worker‐animal interaction. Am. J. Ind. Med. 59:236–244, 2016. © 2015 Wiley Periodicals, Inc.